Evaluation of a Mixed Meal Test for Diagnosis and Characterization of PancrEaTogEniC DiabeTes Secondary to Pancreatic Cancer and Chronic Pancreatitis: Rationale and Methodology for the DETECT Study From the Consortium for the Study of Chronic Pancreatitis, Diabetes, and Pancreatic Cancer - Hart, Phil A. (Pancreas, 2018)
Pancreatogenic diabetes mellitus is most commonly the result of chronic pancreatitis, but can also occur secondary to pancreatic cancer. The early identification of pancreatogenic diabetes and distinction from the more prevalent type 2 diabetes is clinically significant; however, currently there is no validated method to differentiate these diabetes subtypes. We describe a study, “Evaluation of a Mixed Meal Test for Diagnosis and Characterization of PancrEaTogEniC DiabeTes Secondary to Pancreatic Cancer and Chronic Pancreatitis: the DETECT study,” which seeks to address this knowledge gap. The DETECT study is a multicenter study that will examine differences in hormone and glucose excursions following a mixed meal test. The study will also create a biorepository that will be used to evaluate novel diagnostic biomarkers for differentiating these diabetes subtypes.